Reidentification of hybridization events with transcriptomic data and phylogenomic study in Seabuckthorn - Hui Zhang; Zhiqi Wang; Xue Su; Dong Han; Lujie Yang; Ying Zhang; Jing Fang; Jingyuan Wang; Kun Sun (Scientific Reports)
Abstract Natural hybridization in sea buckthorn (Hippophae spp.) is well documented. While the parental species involved in these events have been identified, distinctions between F1 hybrids and later-generation (Fn) hybrids remain insufficiently explored, and their genetic compositions are not yet fully understood. In this study, we employed transcriptomic data and reference genomes to identify Fn hybrids in two natural hybrid populations, confirming eight individuals—including H. goniocarpa Lian. X. L. Chen et K. Sun and four members of a hybrid swarm from Qinghai, China—as F1 hybrids. These findings support the hypothesis that H. goniocarpa is not a distinct species, but rather an F1 hybrid within the genus. Additionally, we discuss limitations specific to SNP calling from transcriptomic data—such as allele-specific expression and low transcript abundance—which may lead to the misclassification of heterozygous sites as homozygous. Finally, we constructed the first phylogenomic tree of the Hippophae genus using transcriptomic data and performed a comparative analysis of interspecific relationships based on SNP and indel markers derived from the same dataset.